PENGARUH KEPUASAN GAJI TERHADAP TURNOVER INTENTIONS DI HOTEL KERATON JIMBARAN RESORT & SPA - Ni Putu Widiastuti (STIE BIITM, 2018)
High rate of turnover leads to adverse effect to an organization. Such problem is likely generating instability and uncertainty towards employment condition and human resources cost rise in forms of training invested to them, recruitment and newly built training programs. High turnover, in addition, also results in organizational ineffectiveness because it loses experienced employees as well as spends much time in training new, inexperienced employees. This study aims to analyze the effect of salary satisfaction, work satisfaction and organizational commitment on withdrawal intention and to analyze the most affective variabel on withdrawal intention. There are 135 respondents for the samples and data analysis during the research is held by using SEM and AMOS 20.0 program. According to the analysis, it is concluded as the followings: salary satisfaction has a negative significant effect on turnover (CR = -2,658). In efforts of decreasing turnover rate, Keraton Jimbaran Resort & Spa should improve its salary rate granted to the employees.